Core Palliative Care Competencies for Undergraduate Nursing Education: International Multisite Research Using Online Nominal Group Technique - Mitrea Nicoleta (My University, 2024)
Background: Nurses should have appropriate education and required competencies to provide high-quality palliative care. The aim of this international multisite study was to list and evaluate core palliative care competencies that European nurses need to achieve in their education to provide palliative care. Methods: The Nominal Group Technique (NGT) was used as a data collection method. NGT meetings were organized in four European countries. Targeted groups of palliative care professionals with diverse contextual and professional backgrounds participated in the NGTs. The research question was: “What are the core competencies in palliative care that need to be achieved during undergraduate nursing education?” Data analysis was done in two stages: grouping the top 10 answers based on similarities and thematic synthesis based on all the ideas produced during the NGTs. Results: Palliative care core competencies based on the research were (1) competence in the characteristics of palliative care; (2) competence in decision-making and enabling palliative care; (3) symptom management competence in palliative care; (4) competence in holistic support in palliative care; (5) active person- and family-centered communication competence in palliative care; (6) competence in empathy in palliative care; (7) spiritual competence in palliative care; (8) competence in ethical and legal issues in palliative care; (9) teamwork competence in palliative care; and (10) self-awareness and self-reflection competence in palliative care. Conclusions: It was possible to find differences and similarities in the top 10 palliative care core competencies from different countries. Thematic synthesis of all the data showed that there were various competencies needed for nursing students to provide quality palliative care.
Keywords: palliative care; nursing; competencies